Beneficial Effects Induced by a Proprietary Blend of a New Bromelain-Based Polyenzymatic Complex Plus N-Acetylcysteine in Urinary Tract Infections: Results from In Vitro and Ex Vivo Studies - Lucia Recinella; Morena Pinti; Maria Loreta Libero; Silvia Di Lodovico; Serena Veschi; Anna Piro; Daniele Generali; Alessandra Acquaviva; Nilofar Nilofar; Giustino Orlando; Annalisa Chiavaroli; Claudio Ferrante; et al. (MDPI AG, 2024)
Background/Objectives: Urinary tract infections (UTIs) are infections that involve the urethra, bladder, and, in much more severe cases, even kidneys. These infections represent one of the most common diseases worldwide. Various pathogens are responsible for this condition, the most common being Escherichia coli (E. coli). Bromelain is a proteolytic complex obtained from the stem and stalk of Ananas comosus (L.) Merr. showing several beneficial activities. In addition to bromelain, N-acetylcysteine (NAC) has also been used. Methods: The purpose of this experiment was to evaluate the antibacterial, anti-motility, and anti-biofilm effects of a new polyenzymatic complex (DIF17BRO®) in combination with NAC (the Formulation) on various strains of E. coli isolated from patients with UTIs. Subsequently, the anti-inflammatory and antioxidant effects of the Formulation were studied in an ex vivo model of cystitis, using bladder samples from mice exposed to E. coli lipopolysaccharide (LPS). Results: Our results showed that the Formulation significantly affects the capability of bacteria to form biofilm and reduces the bacteria amount in the mature biofilm. Moreover, it combines the interesting properties of NAC and a polyenzyme plant complex based on bromelain in a right dose to affect the E. coli adhesion capability. Finally, the Formulation exhibited protective effects, as confirmed by the inhibitory activities on multiple inflammatory and oxidative stress-related pathways on bladder specimens exposed to LPS. Conclusions: This blend of active compounds could represent a promising and versatile approach to use to overcome the limitations associated with conventional therapies.